2014
DOI: 10.1098/rstb.2013.0352
|View full text |Cite
|
Sign up to set email alerts
|

Ecological studies of polyploidy in the 100 years following its discovery

Abstract: Polyploidy is a mutation with profound phenotypic consequences and thus hypothesized to have transformative effects in plant ecology. This is most often considered in the context of geographical and environmental distributions—as achieved from divergence of physiological and life-history traits—but may also include species interactions and biological invasion. This paper presents a historical overview of hypotheses and empirical data regarding the ecology of polyploids. Early researchers of polyploidy (1910s–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
243
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(253 citation statements)
references
References 284 publications
(702 reference statements)
5
243
1
4
Order By: Relevance
“…The two root-feeding weevils D. stolidum and C. trisulcatus were both more often found in L. vulgare than in L. ircutianum populations while the opposite pattern was found for the rootgalling tephritid fly O. nebulosa. Yet, in contrast to a generally larger plant size of polyploids (Ramsey and Ramsey 2014), the diploid L. vulgare produced more shoots and flower heads than the tetraploid L. ircutianum and our results suggest that the higher number of shoots of L. vulgare contributed to the higher attack rates of L. vulgare by D. stolidum and C. trisulcatus. Several field studies found differences in herbivore attack between closely related taxa differing in ploidy level (Thompson et al 1997;Nuismer and Thompson 2001;Münzbergová 2006;Arvanitis et al 2008;Halverson et al 2008;Arvanitis et al 2010;Richardson and Hanks 2011;Münzbergová et al 2015).…”
Section: Comparison Of European L Vulgare and L Ircutianummentioning
confidence: 42%
“…The two root-feeding weevils D. stolidum and C. trisulcatus were both more often found in L. vulgare than in L. ircutianum populations while the opposite pattern was found for the rootgalling tephritid fly O. nebulosa. Yet, in contrast to a generally larger plant size of polyploids (Ramsey and Ramsey 2014), the diploid L. vulgare produced more shoots and flower heads than the tetraploid L. ircutianum and our results suggest that the higher number of shoots of L. vulgare contributed to the higher attack rates of L. vulgare by D. stolidum and C. trisulcatus. Several field studies found differences in herbivore attack between closely related taxa differing in ploidy level (Thompson et al 1997;Nuismer and Thompson 2001;Münzbergová 2006;Arvanitis et al 2008;Halverson et al 2008;Arvanitis et al 2010;Richardson and Hanks 2011;Münzbergová et al 2015).…”
Section: Comparison Of European L Vulgare and L Ircutianummentioning
confidence: 42%
“…These differences in genome size reflect underlying genomic processes such as (retro)transposon amplification and deletion and whole-genome duplication (polyploidy). All of these processes can influence molecular evolution, gene expression, and organismal phenotype (Neiman et al, 2009(Neiman et al, , 2013aGerstein, 2013;Mayfield-Jones et al, 2013;Ramsey and Ramsey, 2014;Dodsworth et al, 2015;Selmecki et al, 2015;Soltis and Soltis, 2016). Polyploidy in particular has been implicated in the remarkably successful radiations of angiosperms (Soltis et al, 2009;Jiao et al, 2011;Albert et al, 2013;Tank et al, 2015;Van de Peer et al, 2017) and teleost fish (Van de Peer et al, 2009;Braasch and Postlethwait, 2012).…”
Section: Future Research Prioritiesmentioning
confidence: 99%
“…Gottlieb ([2], p. 91) A common phenomenon in plant evolution is the hybridization of two diploid species, accompanied by whole-genome duplication, to produce an allotetraploid species with two homoeologous sub-genomes (see contributions by Soltis et al [3], Ramsey & Ramsey [4], Vanneste et al [5], Jiao & Paterson [6]). New allotetraploids contain duplicate copies of every gene that was present in both their parents.…”
Section: Introductionmentioning
confidence: 99%